1999
DOI: 10.1038/sj.leu.2401260
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected mortality from the use of E. coli L-asparaginase during remission induction therapy for childhood acute lymphoblastic leukemia: a report from the Taiwan Pediatric Oncology Group

Abstract: The relative efficacy and toxicity of E. coli L-asparaginase and epidoxorubicin used in remission induction therapy for childhood acute lymphoblastic leukemia (ALL) were assessed in a randomized trial conducted in Taiwan. All patients had standard-risk ALL, defined as a leukocyte count Ͻ10 × 10 9 /l and were aged between 1 and 2 or 7 and 10 years, or a leukocyte count Ͻ50 × 10 9 /l and were aged between 2 and 7 years, without evidence of a T cell or mature B cell immunophenotype, central nervous system leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…We hypothesize that individual genetic difference in response to Asp depletion may account for such variation. Since our four patients received two different Asp preparations (1 with Elspar, 3 with Leunase), manufacturing differences do not appear to be a contributory factor [7].…”
mentioning
confidence: 89%
“…We hypothesize that individual genetic difference in response to Asp depletion may account for such variation. Since our four patients received two different Asp preparations (1 with Elspar, 3 with Leunase), manufacturing differences do not appear to be a contributory factor [7].…”
mentioning
confidence: 89%
“…1,3 Table 1 shows the risk classification system used to stratify patients into very high risk (VHR; 'high risk' in other studies), high risk (HR; 'intermediate risk' in other studies), and SR groups. Tables 2 and 3 summarize the treatment of protocols TPOG-2002 SR and HR, and of protocols TPOG-2002 VHR, respectively.…”
Section: Treatmentmentioning
confidence: 99%
“…As our earlier experience had revealed that Escherichia coli L-asparaginase (Leunase) at 10 000 IU/m 2 per dose led to a higher mortality rate, 1 this agent has been used at 5000 IU/m 2 since 1997. In the subsequent study, TPOG- ALL-2002ALL- (2002ALL- -2007, we limited the use of cranial irradiation, replacing it with early intensification of triple intrathecal therapy; 2,3 SR patients were randomized to receive single or double reinduction therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic analysis of the blast cells was performed using a direct method or short-term unstimulated cultures. The immunophenotyping was performed by flow cytometry using monoclonal antibodies against HLA-DR, CD34, CD19, CD10, cIgM, sIgM, CD7, CD2, CD5, CD3, CD13, CD14, CD33, CD41, and CD61 [22]. Written informed consent was obtained from parents or their legal guardians.…”
Section: Patients and Materialsmentioning
confidence: 99%